Duloxetine and 8-OH-DPAT, but not fluoxetine, reduce depression-like behaviour in an animal model of chronic neuropathic pain - Hu, Bing; Treede, Rolf-Detlef (Neuroscience letters, 2016)
The current study assessed whether antidepressant and/or antinociceptive drugs, duloxetine, fluoxetine as well as (±)-8-hydroxy-2-[di-n-propylamino] tetralin (8-OH-DPAT), are able to reverse depression-like behaviour in animals with chronic neuropathic pain. Chronic constriction injury (CCI) of the sciatic nerve in rats was selected as neuropathic pain model. Mechanical hypersensitivity and depression-like behaviour were evaluated 4 weeks after surgery by “electronic algometer” and forced swimming test (FST), which measured the time of immobility, and active behaviours climbing and swimming. The selective noradrenergic and serotonergic uptake blocker duloxetine (20mg/kg) and the selective 5-HT1A agonist 8-OH-DPAT (0.5mg/kg) significantly reversed both mechanical hypersensitivity and depression-like behaviour in CCI animals. Duloxetine significantly reversed depression-like behaviour in CCI rats by increasing the time of climbing and swimming, while 8-OH-DPAT attenuated depression-like behaviour mainly by increasing the time of swimming. However, the selective serotonergic uptake blocker fluoxetine (20mg/kg) failed to attenuate mechanical hypersensitivity and depression-like behaviour, possibly due to confounding pro-nociceptive actions at 5-HT3 receptors. These data suggest to target noradrenergic and 5-HT1A receptors for treatment of chronic pain and its comorbidity depression.
Gesehen am 07.06.2019